Medication errors in paediatric patients: the role of the clinical pharmacist - Alsenani, Ahmed (2015)
Six electronic databases were searched and 153 studies which identified the number or the rate of paediatric medication errors were identified; mainly from the US. These studies were compared to identify factors responsible for the great variations seen in reported error rates (Chapter 2). The most important factors were the use of different denominators, different definitions of medication errors, and the use of different methods of data collection.